2018
DOI: 10.1111/jfbc.12568
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiling and in vitro antioxidant, anticholinesterase, and antimonoamine oxidase properties of aqueous extract of African star apple (Chrysophyllum albidum) fruit parts

Abstract: African star apple is a tropical edible fruit that is widely consumed among Nigerians. This present study investigated the antioxidant, anticholinesterase, and antimonoamine oxidase properties of African star apple fruit parts (flesh pulp, seed coat, and back coat) in vitro. The aqueous extracts of different parts were prepared. Thereafter, the effect on cholinesterases (acetylcholinesterase [AChE] and butyrylcholinesterase [BChE]) and monoamine oxidase (MAO) activities and antioxidant potentials (1,1-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…It was also shown that administration of metformin and the supplemented diets lowered the activity of arginase in the testis and epididymis and were significantly different (p < 5%) from the diabetic untreated group while 10% supplementation gave the more pronounced effect on the arginase activity in the testis only. This may result from the presence of the phenolic compounds in the supplemented diets as previously reported by Oboh, Adebayo, Ejakpovi, Ogunsuyi, and Boligon (2018). According to Oboh et al (2018), the fruit pulp was reported to be rich in phenolic compounds such as caffeic acid, chlorogenic acid, and quercetin.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It was also shown that administration of metformin and the supplemented diets lowered the activity of arginase in the testis and epididymis and were significantly different (p < 5%) from the diabetic untreated group while 10% supplementation gave the more pronounced effect on the arginase activity in the testis only. This may result from the presence of the phenolic compounds in the supplemented diets as previously reported by Oboh, Adebayo, Ejakpovi, Ogunsuyi, and Boligon (2018). According to Oboh et al (2018), the fruit pulp was reported to be rich in phenolic compounds such as caffeic acid, chlorogenic acid, and quercetin.…”
Section: Discussionmentioning
confidence: 64%
“…This may result from the presence of the phenolic compounds in the supplemented diets as previously reported by Oboh, Adebayo, Ejakpovi, Ogunsuyi, and Boligon (2018). According to Oboh et al (2018), the fruit pulp was reported to be rich in phenolic compounds such as caffeic acid, chlorogenic acid, and quercetin.…”
Section: Discussionmentioning
confidence: 64%
“…Analysis of phenolic compounds present in orange peels was carried out using high‐performance liquid chromatography as previously described by Oboh, Adebayo, Ejakpovi, Ogunsuyi, and Boligon (). The chromatography peaks were confirmed by comparing its retention time with those of reference standards and by DAD spectra (200–500 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of phenolic components of eggplant fruits collected from Ibadan and Uyo was performed according to the standard procedure of Oboh, Adebayo, Ejakpovi, Ogunsuyi, and Boligon (2018). Eggplant extract (12 mg/ml) was injected by means of a model SIL-20A Shimadzu auto sampler.…”
Section: Analysis Of Phenolic Components Using High-performance Liqmentioning
confidence: 99%